2023
DOI: 10.3390/nu15112454
|View full text |Cite
|
Sign up to set email alerts
|

RAASi Therapy Attenuates the Association between 24-h Urinary Potassium Excretion and Dietary Potassium Intake in CKD Patients

Abstract: The aim of this study was to evaluate urinary potassium (K) excretion as a reliable marker of dietary K intake, in a cohort of CKD patients with or without Renin-Angiotensin-Aldosterone System (RAAS) inhibitor therapy. One hundred and thirty-eight consecutive out-patients (51 f and 87 m) aged 60 ± 13 years and affected by CKD stage 3–4, who were metabolically and nutritionally stable, entered the study between November 2021 and October 2022. No difference was observed between patients with (n = 85) or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Notably, guidelines on CKD management [ 19 ] highlight the role of dietary potassium intake in CKD, recommending the assessment of dietary potassium intake in CKD patients, particularly those with potential hyperkalaemia [ 20 ]. In this context, two other studies included in this Special Issue explored different aspects of the assessment of dietary potassium intake in patients with CKD [ 21 , 22 ]. Moreover, since the mechanisms of potassium homeostasis and excretion are impaired in these individuals, 24 h urine collection (the recognised gold standard for monitoring potassium intake [ 23 ]) may not be reliable to evaluate potassium intake in this setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, guidelines on CKD management [ 19 ] highlight the role of dietary potassium intake in CKD, recommending the assessment of dietary potassium intake in CKD patients, particularly those with potential hyperkalaemia [ 20 ]. In this context, two other studies included in this Special Issue explored different aspects of the assessment of dietary potassium intake in patients with CKD [ 21 , 22 ]. Moreover, since the mechanisms of potassium homeostasis and excretion are impaired in these individuals, 24 h urine collection (the recognised gold standard for monitoring potassium intake [ 23 ]) may not be reliable to evaluate potassium intake in this setting.…”
mentioning
confidence: 99%
“…In particular, one study evaluated the relationship between urinary potassium excretion (via 24 h urine collection) and dietary potassium intake (via a questionnaire) in a cohort of stage 3–4 CKD patients with or without RAAS inhibitor therapy [ 21 ]. The main analysis, which included 138 patients (60 ± 13 years), indicated that urinary potassium excretion was significantly, but weakly, associated with the glomerular filtration rate and dietary potassium intake.…”
mentioning
confidence: 99%